A prospective study on incisional hernia, its incidence, etiology and management in a tertiary care hospital of Odisha - Pattanaik, S. K.; Firodous, Afroza; John, Ajax; Pattnaik, Harsha; Mishra, Biplab; Sahu, Biswajit (International Surgery Journal, 2019)
Background: Incisional hernia (IH) is defined as the hernia protruding through incompletely healed abdominal surgical wound. Management of IH can be preventive (avoidance of infection and suture line tension, proper abdominal wound closure) or operative (anatomical reconstruction or repair with synthetic non-absorbable mesh either by open or laparoscopy method). Methods: A descriptive prospective observational study on 51 patients with age >15 yrs was conducted in the Department of General Surgery, SCB Medical College and Hospital, Cuttack from August 2015 to August 2017. Diagnosis was made with clinical history, physical examination, X-ray abdomen and USG abdomen. The patients underwent different surgical procedures depending on size of defect, patient’s consent and expertise available. Post-operative complications were noted and patients were followed up to 1 year for any recurrence. Results: 28 males and 23 females were included. The mean age was 42.3 years. Most common cause of IH was post-operative wound infection (47.1%). Maximum cases were following emergency surgery (88.2%). Midline incision contributes maximum number (52.9%) followed by Pfannenstiel incision (25.4%). Open hernioplasty was the most common procedure (58.8%) followed by anatomical repair (19.6%) and laparoscopic hernioplasty (15.6%). Recurrence with suture repair was 10%, open mesh repair 3.3% and no recurrence was observed following laparoscopic repair. Conclusions: Prevention of IH is to be taken care of, by avoiding infection during index operation with thorough peritoneal toileting, proper surgical techniques and appropriate antibiotics. Although laparoscopic mesh repair needs more operating time and skill, it has lesser blood loss, hospital stay and recurrence rate when compared to other procedures.